AKHLAK KEPADA DIRI SENDIRI - Muhrin, Muhrin (Tarbiyah Islamiyah: Jurnal Ilmiah Pendidikan Agama Islam, 2020)
ABSTRACT: Today, the morale of this nation is getting destroyed and lost. This is evidenced by the immoral behaviors carried out by the Indonesian people, especially young people. Immoral attitudes are now increasingly rampant in people's lives and have even been considered normal and natural in people's lives. This is inseparable from the mistakes of parents in educating their children who let it go without being provided with religious knowledge which is used as a guide for living in their life in the world. One of the main keys in fixing the morals of this nation is by focusing on the family environment and the need for awareness to every family that moral education, especially moral education, is important to be taught and instilled in a child. In the process of inculcating moral values, moral values must first be instilled in ourselves, because all of these things start from ourselves. Once we are truly embedded in moral values, it can automatically spread in other aspects of life.KEYWORDS: Morals; Self; Behavior ABSTRAK: Dewasa ini, moral bangsa ini semakin hancur dan hilang. Hal ini terbukti dengan adanya perilaku-perilaku amoral yang dilakukan oleh masyarakat Indonesia terutama kaum muda. Sikap amoral yang sekarang semakin merajalela di kehidupan masyarakat dan malah sudah dianggap biasa dan wajar dalam kehidupan masyarakat. Hal ini tidak terlepas dari kesalahan orangtua dalam mendidik anaknya yang membiarkan begitu saja tanpa dibekali adanya pengetahuan-pengetahuan agama yang dijadikan pedoman hidup dalam mengarungi kehidupannya di dunia. Salah satu kunci utama dalam membenahi akhlak bangsa ini yaitu dengan menitikberatkan pada lingkungan keluarga dan perlu penyadaran terhadap setiap keluarga bahwasanya pendidikan akhlak terutama pendidikan akhlak penting untuk diajarkan dan ditanamkan dalam diri seorang anak. Dalam proses penanaman nilai akhlak ini haruslah pertama kali ditanamkan nilai-nilai akhlak terhadap diri sendiri, karena semua hal itu dimulai dari diri kita sendiri. Setelah diri kita benar-benar tertanam nilai akhlak maka secara otomatis dapat menjalar dalam aspek-aspek kehidupan yang lain.KATA KUNCI: Akhlak; Diri Sendiri; Perilaku.